Screening in colorectal cancer First study of the asymptomatic population in Uruguay - Montano, Daniel; Fenocchi, Eduardo; Martínez, Luz; Rondán, Mariela; Olano, Carolina (Cirugía del Uruguay, 2000)
We present the first colorrectal cancer screening done in our country Colorectal cancer is the second cause of dead far cancer in our country and is the first digestive cancer. The screening is the best way far diagnosis of early colorectal cancer and premalignant /esions. We use inmunological test in arder to detect the fecal occult blood because it have a very high specificity and sensibility over 90%. Between Ju/y 3 and October 16 of 1996 1.000 patients were included. Those patients were over 50 years old and they must not have any digestive symptom. More than 80,5% (805) complete the study, 14,6% (117) were positive and 70 of them received a colonoscopy We found 75 co/orectal /esions in 48 patients with 28 adenomas.